Argus developer in practice : real estate development modeling in the real world - Havard, Tim M. (Apress, 2014)
This book is a practical guide to using Argus Developer, the world's most widely used real estate development feasibility modeling software. Using practical examples and many case studies, it takes readers beyond basic training and provides the in-depth knowledge required to analyze potential real estate deals and help ensure a profitable development. Argus Developer in Practice fills an important gap in the market. Argus Developer, and its predecessor Circle Developer, has long had a dominant position as the primary real estate development appraisal tool. It is used all over the world on a variety of projects ranging from simple residential projects to huge and complex master planned, mixed-use, commercial, residential, and leisure projects. It also shines when used to appraise "refurbs"-taking an existing building or complex and upgrading it or turning it into something entirely different. Argus Developer in Practice,the first book that concentrates on the practical application and use of the program, goes beyond the manual that comes with it by taking you through the development/project appraisal process step by step. In addition, author Tim Havard has over 25 years of experience in carrying out development appraisals both in practice and in teaching at the postgraduate level in UK and Australian universities. He started using the DOS version of Circle Developer in 1990, then worked for both Circle and Argus training clients on the software in the UK, continental Europe, and the Middle East. Besides showing you how to use the program, Havard shows you how to think like a successful real estate developer. Using an extensive array of screenshots, Argus Developer in Practice delves deeply into practical use of the program by offering case studies of varying complexity that will help real estate professionals not just analyze development projects but also learn how the best minds in real estate analyze a project's potential. You will learn: How to model both simple projects and complex mixed-use and multi-phased investment schemes How to model new uses for existing properties How to think through real estate project problems How to analyze a potential development project in depth By using the program efficiently and making use of its more advanced features, you can help ensure a profitable project without the surprises that accompany most real estate ventures. Argus Developer in Practice therefore provides something priceless-peace of mind.